Comparative Prevalence Rate of Common ENT Disorders in Breast Fed Versus Artificially Fed Babies, and the Influence of Variables - Hameed, Abdul; Sattar, Fazle; Din, Shah; Khan, Saleem (Journal of Postgraduate Medical Institute, 2011)
The Advantages of breast feeding are numerous while the disadvantages of artificial feeding are legendary. Infantile gastroenteritis, hypernatraemic dehydration. Cow's milk protein allergy, lactose intolerance, tetany and atopic dermatitis are just a few to mention in this context. It is also common knowledge that acute infections of the respiratory tract as well as diseases and disorders of the ear, nose, throat are more common in artificially fed babies. Disorders / diseases of the Ear, Nose and Throat are responsible for considerable morbidity among infants and young children (0-5 years). These infants and children present initially to the local Medical practitioners or pediatrician with acute or sub-acute complaints of variable nature. Like feeding difficulties due to cough, nasal obstruction, irritability due to otalgia, and noisy breathing which is often interpreted as asthma. These children may present to the ENT specialist with recurrent or chronic problems like discharging ears, hearing difficulty, or delayed / abnormal speech later in life. Parallel with the declining trend in the incidence of breast feeding (68.46%) in this study) there is an observable increase in the prevalence rate of common ENT disorders / diseases.